Connectivity of core habitat in the Northeastern United States: Parks and protected areas in a landscape context - Goetz, S. J.; Jantz, P.; Jantz, C. A. (Remote Sensing of Environment, 2009)
The exurbanization process, particularly rural residential development, is reducing the amount of roadless areas and remote habitat across the nation, with implications for biodiversity and ecosystem integrity of parks and protected areas. The need for connecting protected areas via existing habitat centers, or relatively undisturbed core areas, is greater than ever as exurbanization expands. Our objective was to make use of nationally available data sets on roads as well as information derived from satellite imagery, including impervious cover of the built environment and forest canopy density, to identify core habitat of the northeastern and mid-Atlantic USA. The identified core habitat areas, which covered 73,730 km(2) across 1177 discrete units, were stratified in terms of land ownership and management, and then analyzed in a landscape context using connectivity metrics derived from graph theory. The connectivity analysis made use of a suitability surface, derived from the land cover information, which approximated the costs incurred by hypothetical animals traversing the landscape. We show that protected areas are frequently identified as core habitat but are typically isolated, albeit sometimes buffered by adjacent multi-use lands (such as state or national forests). Over one third of the core habitat we identified has no protection, and another 42% is subject to motorized recreation or timber extraction. We provide maps showing the relative importance of core habitat areas for potentially connecting existing protected areas, and also provide an example of the vulnerability of connectivity to projected future residential development around one greater park ecosystem.
Keywords: connectivity; Conservation; Graph theory; impervious cover; Land cover change; Landscape ecology; Management; Protected areas; Roadless areas